An assessment of melatonin's therapeutic value in the hypoxic-Ischemic encephalopathy of the newborn - Cardinali, Daniel Pedro (2019)
Fil: Cardinali, Daniel Pedro. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina